Tunable quantum photoinitiators for radical photopolymerization - Shukla S.; Pandey P.C.; Narayan R.J. (My University, 2025)
This review describes the use of nanocrystal-based photocatalysts as quantum photoiniti-ators, including semiconductor nanocrystals (e.g., metal oxides, metal sulfides, quantum dots), carbon dots, graphene-based nanohybrids, plasmonic nanocomposites with organic photoinitiators, and tunable upconverting nanocomposites. The optoelectronic properties, cross-linking be-havior, and mechanism of action of quantum photoinitiators are considered. The challenges and prospects associated with the use of quantum photoinitiators for processes such as radical polymer-ization, reversible deactivation radical polymerization, and photoinduced atom transfer radical polymerization are reviewed. Due to their unique capabilities, we forsee a growing role for quantum photoinitiators over the coming years. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.